Urinary Neurotransmitter Patterns Are Altered in Canine Epilepsy - Schmidt, Teresa; Meller, Sebastian; Talbot, Steven R.; Berk, Benjamin A.; Law, Tsz H.; Hobbs, Sarah L.; Meyerhoff, Nina; Packer, Rowena M. A.; Volk, Holger A. (Frontiers in Veterinary Science, 2022)
Epilepsy is the most common chronic neurological disease in humans and dogs. Epilepsy is thought to be caused by an imbalance of excitatory and inhibitory neurotransmission. Intact neurotransmitters are transported from the central nervous system to the periphery, from where they are subsequently excreted through the urine. In human medicine, non-invasive urinary neurotransmitter analysis is used to manage psychological diseases, but not as yet for epilepsy. The current study aimed to investigate if urinary neurotransmitter profiles differ between dogs with epilepsy and healthy controls. A total of 223 urine samples were analysed from 63 dogs diagnosed with idiopathic epilepsy and 127 control dogs without epilepsy. The quantification of nine urinary neurotransmitters was performed utilising mass spectrometry technology. A significant difference between urinary neurotransmitter levels (glycine, serotonin, norepinephrine/epinephrine ratio, ɤ-aminobutyric acid/glutamate ratio) of dogs diagnosed with idiopathic epilepsy and the control group was found, when sex and neutering status were accounted for. Furthermore, an influence of antiseizure drug treatment upon the urinary neurotransmitter profile of serotonin and ɤ-aminobutyric acid concentration was revealed. This study demonstrated that the imbalances in the neurotransmitter system that causes epileptic seizures also leads to altered neurotransmitter elimination in the urine of affected dogs. Urinary neurotransmitters have the potential to serve as valuable biomarkers for diagnostics and treatment monitoring in canine epilepsy. However, more research on this topic needs to be undertaken to understand better the association between neurotransmitter deviations in the brain and urine neurotransmitter concentrations in dogs with idiopathic epilepsy.